Collective Consciousness to Pursue Gender Equality in The Ministry of Utmost Happiness - Jahan, Nusrat; Rahman, Muhammad Mushfiqur (European Publisher, 2019)
The Ministry of Utmost Happiness tells the story of the marginalized people who are abused but share a collective understanding of different social norms. Gender inequality is a multi-layered dispute which states that there is discrimination among genders and it prevents the path of getting basic rights of the human being. On the other hand, gender equality eliminates violence, harmful practices and discrimination against all women and girls. Focusing on the theory of collective consciousness, this paper explores the question of gender equality in Arundhati Roy’s The Ministry of Utmost Happiness. Non-structural qualitative analysis is applied in this paper to distinguish past trends and forecast future models. Arundhati Roy precisely points out that the shared beliefs, ideas, attitudes can operate strongly as a powerful force to bring down the gender inequality in her The Ministry of Utmost Happiness. The author establishes that the collected voices can only stand together to make a difference in the world of injustice in this novel. This paper investigates how the combined innate craving for strength, justice and power builds up a gathering in a graveyard and how it works in the pursuit of gender justice.